Mechanisms of asymmetric cell divisions in Drosophila melanogaster neuroblasts - X Jiang; C Tang; H Gao; H Cui (Invertebrate Survival Journal, 2014)
Stem cells possess the properties of self-renewal and differentiation, and mainly rely on two strategies for division, including symmetric and asymmetric cell divisions. In this review, we summarize the latest progress on asymmetric cell divisions in Drosophila melanogaster neuroblasts (NBs), which focus on the establishment of cell polarity, mitotic spindle orientation, the asymmetric segregation of cell fate determinants as well as cell-cycle control. Here we also introduce five major cell fate determinants, including Numb, Prospero, Brat, Miranda, and Pon, which are thought to be unequally segregated to the ganglion mother cells (GMCs) and play an important role in the formation of stem cell-derived tumors